UNITING COMPATRIOTS ABROAD AROUND A SINGLE HOMELAND IS AT THE LEVEL OF STATE POLICY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In order to unite compatriots living abroad, the public fund “Vatandoshlar” was established. It is known that on August 11, 2021, the decision of the President of the Republic of Uzbekistan on the establishment of the public fund “Vatandoshlar” was signed. The main goal of this historic decision is to further unite our compatriots living abroad around their motherland, to increase the sense of pride in the country in their hearts and minds, to preserve national identity, to support compatriots and public associations formed by them, and to implement a number of specific directions.